ETHNOBOTANICAL SURVEY OF COSMETIC PLANTS USED IN KATSINA STATE, FORMULATION OF NATURAL POLY HERBAL LIGHTENING CREAM USING Curcuma longa AND Curcubita pepo EXTRACTS - Kankara, Sulaiman Sani; Ahmad, Maimuna; Lawal, Umar (FUDMA JOURNAL OF SCIENCES, 2023)
This study aimed to conduct an ethnobotanical survey of cosmetic plants in Katsina State and formulate a polyherbal lightening cream using Curcuma longa and Cucurbita pepo extracts. The Research involved two main aspects. A semi-structured interview was used to gather information on the use cosmetic plants.23 plants were identified including: Aloe vera, Calatropis procera, Magnifera indica, Carica papaya,Allium cepa. These plants were found to have various cosmetic benefits such as skin lightening, weight loss, hair treatment, acne treatment. An attempt was made to formulate a safe lightening cream using plants extract Curcuma longa and Cucurbita pepo. The formulation process involved: procurement of plants, preparation of the extracts (powdered extracts using Ethanol, cold press method was used for the oil extract). The resulting polyherbal lightening cream was evaluated for its skin related properties, such as skin lightening and skin health. The study demonstrated the potential of medicinal plants in skincare and the possibility of developing effective polyherbal cosmetic pro.